Detection of Hypoxaemia by Arterial Blood Gas in Children with Acute Lower Respiratory Illness (Eastern Medical College Journal, 2025)
Background: Acute lower respiratory illness (ALRI) contributes to significant mortality in developing countries and the majority of this is secondary to hypoxemia. Early detection of hypoxemia and treatment improves the outcome in these children. The aim of the study is to detection of hypoxaemia by analysis of arterial blood gas in children with ALRI admitted to Paediatrics ward of Chattogram Medical College Hospital (CMCH), Chattogram, Bangladesh.Materials and methods: Ethical permission was taken from the Institutional Review Board of Chittagong Medical College (CMC) for this study. In this hospital based cross sectional study a total of 100 patients with ALRI aged between 2 to 60 months in paediatrics ward of CMCH were included. Besides demographic factors (age, sex, place of residence) and presenting symptoms were recorded. Oxygen saturation of these children was recorded by ABG analysis to detect hypoxaemia. Children having PaO2